17?-hydroxysteroid dehydrogenase-3 deficiency in disorder of sex development - Rahman, MH; Hoque, MA; Mannan, MA (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):170-174 The abstract of this article is available on the PubMed website